Effects of seat-tube angle on the metabolic cost of the cycle-run transition in triathletes - Jackson, K. J.; Mulcare, J. A.; Duncan, R. C. (Journal of Exercise Physiology online, 2008)
The purpose of this study was to investigate the effects of two different (73° and 81°) seat-tube angles (STA) on cardiorespiratory measures during cycling and a subsequent treadmill run. Ten male triathletes completed a 40-minute "time-trial" at a pre-determined workload on a cycle ergometer at 73° and 81° STAs and immediately transitioned to running on a treadmill at a pre-determined pace. Oxygen consumption (VO2) and heart rate (HR) data were collected during the last 5-minutes of cycling and first 5-minutes of running. Consistent hip and knee angles were maintained between cycling conditions. There were no differences in VO2 for cycling or running between the 73° and 81° STA conditions. Heart rate was significantly lower during cycling at the 73° STA (p<0.05). There were no differences in running heart rates. These results suggest that if bicycle seat-tube angle is changed, but hip and knee angles remain consistent, there is no difference in the metabolic cost of cycling or a subsequent treadmill run. ABSTRACT FROM AUTHOR